The tech advantage: exploring technological determinants of social media marketing adoption in Pakistani small and medium startups - Arsalan Ahmed; Sara Rashid; Norizan Mat Saad; Muhammad Waqas Rana; Ikhtiar Ahmed Khoso; Zeshan Ahmed (Journal of Innovation and Entrepreneurship)
Abstract This study investigates the technological determinants influencing social media marketing (SMM) adoption among Pakistani Small and Medium Startups (SMS), with a focus on the mediating role of technology knowledge. Utilizing the technology–organization–environment (TOE) Framework, the research examines the impact of technology compatibility, complexity, cost, infrastructure, and knowledge on the adoption of SMM. Data were collected through a survey from 386 startups based in Karachi, providing a robust basis for analysis. The findings reveal that technology knowledge significantly mediates the relationships between these technological factors and SMM adoption, enabling startups to better navigate the complexities associated with SMM. Results show that technology compatibility, infrastructure, and knowledge positively influence SMM adoption, while technology complexity and cost are not significant barriers for startups. This contrasts with traditional SMEs, where these factors often hinder SMM adoption efforts. The study highlights the distinct nature of SMSs and the necessity of tailoring technology adoption strategies to their unique needs. The practical implications of this research highlight the importance of investing in technology training and infrastructure to empower startups with the necessary tools and skills for leveraging SMM effectively. This approach not only enhances their market competitiveness but also supports their growth in the digital economy. Overall, this research contributes to a deeper understanding of how technological determinants affect SMM adoption in startups, providing valuable insights for both practitioners and policymakers aiming to promote a robust digital startup ecosystem.